Книга как средство коммуникации - Овчинникова, Альбина Петровна; Овчинникова, Альбіна Петрівна; Ovchinnikova, Al'bina (My University, 2012)
Genesis of reading as mean of communication investigated in the article. The analysis of this mean allows finding the different functions of reading aloud and reading to oneself. A difference between the educational reading and consumer reading is substantial
Овчинникова А. П Книга как средство коммуникации / А. П. Овчинникова // Наукові праці Національного університету «Одеська юридична академія» : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; відпов. за вип. В. М. Дрьомін ; МОН України, НУ ОЮА. – Одеса : Юрид. л-ра, 2012. – Т. 11. – С. 305-313.
Keywords: канон чтения; культура; практики чтения; канон читання; практики читання; canon of reading; culture; practices of reading